Experience measuring performance improvement in multiphase picture archiving and communications systems implementations...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Reed G; Reed DH (Journal of Digital Imaging)
When planning a picture archiving and communications system (PACS) implementation and determining which equipment will be implemented in earlier and later phases, collection and analysis of selected data will aid in setting implementation priorities. If baseline data are acquired relative to performance objectives, the same information used for implementation planning can be used to measure performance improvement and outcomes. The main categories of data to choose from are: (1) financial data; (2) productivity data; (3) operational parameters; (4) clinical data; and (5) information about customer satisfaction. In the authors' experience, detailed workflow data have not proved valuable in measuring PACS performance and outcomes. Reviewing only one category of data in planning will not provide adequate basis for targeting operational improvements that will lead to the most significant gains. Quality improvement takes into account all factors in production: human capacity, materials, operating capital and assets. Once we have identified key areas of focus for quality improvement in each phase, we can translate objectives into implementation requirements and finally into detailed functional and performance requirements. Here, Integration Resources reports its experience measuring PACS performance relative to phased implementation strategies for three large medical centers. Each medical center had its own objectives for overcoming image management, physical/geographical, and functional/technical barriers. The report outlines (1) principal financial and nonfinancial measures used as performance indicators; (2) implementation strategies chosen by each of the three medical centers; and (3) the results of those strategies as compared with baseline data. Copyright (c) 1999 by W.B. Saunders Company